Effect of konjac glucomannan on gut microbiota from hyperuricemia subjects in vitro: fermentation characteristics and inhibitory xanthine oxidase activity - Deng, Jie; Zhou, Kai; Feng, Caimin; Bao, Yilu; Zhang, Zhiming; Luo, Wenfeng; Li, Meiying (Frontiers in Nutrition, 2024)
The disorder of uric acid metabolism is closely associated with gut microbiota and short chain fatty acids (SCFAs) dysregulation, but the biological mechanism is unclear, limiting the development of uric acid-lowering active polysaccharides. Konjac glucomannan (KGM) could attenuate metabolic disturbance of uric acid and modulate the gut microbiota. However, the relationship between uric acid metabolism and gut microbiota is still unknown. Thus, the anaerobic fermentation in vitro was used to investigate the potential mechanism. The results showed that KGM could be utilized and degraded by gut microbiota from hyperuricemia (HUA) subjects and modulate the composition and structure of HUA gut microbiota toward to that of healthy group. Besides, KGM showed a superior modulated effect on HUA gut microbiota by increasing Megasphaera, Faecalibacterium, Lachnoclostridium, Lachnospiraceae, Anaerostipes and Ruminococcus and decreasing Butyricicoccus, Eisenbergiella and Enterococcus level. Furthermore, the fermentation solution of KGM showed inhibitory effect on xanthine oxidase (XOD) enzyme activity, which might be due to the metabolites such as SCFAs. Thus, KGM can be expected as novel prebiotics for treatment of HUA via modulating gut microbiota and promoting the production of SCFAs.